2020
DOI: 10.2196/21982
|View full text |Cite
|
Sign up to set email alerts
|

User Experience of a Chatbot Questionnaire Versus a Regular Computer Questionnaire: Prospective Comparative Study

Abstract: Background Respondent engagement of questionnaires in health care is fundamental to ensure adequate response rates for the evaluation of services and quality of care. Conventional survey designs are often perceived as dull and unengaging, resulting in negative respondent behavior. It is necessary to make completing a questionnaire attractive and motivating. Objective The aim of this study is to compare the user experience of a chatbot questionnaire, whi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 22 publications
(26 reference statements)
1
10
0
Order By: Relevance
“…Wambsganss et al 54 found that participants using chatbot surveys showed higher response quality and social presence than a web survey. In a health context, Te Pas et al 55 concluded that patients preferred a chatbot questionnaire over a computer questionnaire as the chatbot was faster, although real-time to completion of both questionnaires did not differ. Based on these studies, chatbots are a feasible alternative to traditional online and computer surveys to improve collected data quality and user experience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wambsganss et al 54 found that participants using chatbot surveys showed higher response quality and social presence than a web survey. In a health context, Te Pas et al 55 concluded that patients preferred a chatbot questionnaire over a computer questionnaire as the chatbot was faster, although real-time to completion of both questionnaires did not differ. Based on these studies, chatbots are a feasible alternative to traditional online and computer surveys to improve collected data quality and user experience.…”
Section: Discussionmentioning
confidence: 99%
“…Future Wakamola chatbot improvement should include questions about the quality of sleep, for example, to allow calculation of the Pittsburgh Sleep Quality Index (PSQI), 55 for a better understanding of sleep changes during confinement. 65…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with previous research [30] which argued that a sense of a socially shared experience contributes to a higher compliance rate of ESM tasks. As pointed in existing literature, traditional computergenerated questionnaire is dull and lacking elements to motivate participants, whereas a chatbot-delivered questionnaire could provide more engaging conversational interactions, which can lead to higher quantity and quality of participants' responses to the ESM questions [31].…”
Section: Leveraging Social Companionship Within Esm Designsmentioning
confidence: 99%
“…Recruitment of participants and exposure to target advertisements occur on Facebook. The surveys are disseminated within Facebook Messenger using a chatbot questionnaire, which has been shown to increase user engagement, user satisfaction, and data quality over traditional web surveys [ 17 - 19 ]. The feasibility of Virtual Lab would allow for quick recruitment of participants and delivery of results, as well as easy navigation of a dashboard during data collection, while remaining cost-effective.…”
Section: Introductionmentioning
confidence: 99%